Ferroelastic Control of the Multicolor Emission from a Triply Doped Organic Crystal - DEĞER, CANER; YAVUZ, İLHAN (My University, 2024)
Emission from crystalline organic solids is often quenched by nonemissive energy-transfer deexcitation processes. While dispersion of fluorophores in polymers or other hosts has been used to enhance the emission intensity, this strategy results in randomization of guest orientation and optical losses at grain boundaries. Here, we report the doping of inherently nonemissive single crystals of anilinium bromide with three fluorescent organic molecules. The doping process equips the crystal with emission characteristics that tune from blue to deep orange. The emission intensity can be reversibly modulated by ferroelastic twinning, which causes the material to function as a multiemissive force sensor. This approach opens up new pathways in the manipulation of emissive properties in organic crystals and may have substantial implications for optoelectronic devices and sensors.
Keywords: Kimya Mühendisliği ve Teknolojisi; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Kimya; Temel Bilimler; Mühendislik ve Teknoloji; Chemical Engineering and Technology; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Chemistry; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); Mühendislik; MÜHENDİSLİK, KİMYASAL; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); Life Sciences (LIFE); ENGINEERING; CHEMISTRY; MOLECULAR BIOLOGY & GENETICS; ENGINEERING, CHEMICAL; BIOCHEMISTRY & MOLECULAR BIOLOGY; Kataliz; Fizik Bilimleri; Genel Kimya; Biyokimya; Kolloid ve Yüzey Kimyası; Catalysis; Physical Sciences; General Chemistry; Biochemistry; Colloid and Surface Chemistry